Gender differences in the determinants of maximal anaerobic running power - Nummela, A.; Rusko, H. (Medicine & Science in Sports & Exercise, 1995)
Gender differences in neuromuscular and metabolic components of maximal anaerobic running power were investigated. Sprinters (M = 10, F = 13), who had competed in 400 m events, were evaluated on a treadmill using a step-increased speed until exhaustion. Males had significantly higher maximal anaerobic power than females but the ratio between power at 10 mM of blood lactate (a test of sprinting economy) and maximal anaerobic power was significantly higher for females. Statistically, for males sprinting economy, peak blood lactate, and speed for 30 m were associated with 400 m performance. However, in females 400 m performance was only related to sprinting economy. Implication. The determinants of 400 m running performance were different for males and females. More factors were related to male than female performances. Sprinting economy was related in both sexes indicating that running form is an important coaching focus. Females would be better served by coaching programs that focus on technique while males also would be well served with a technique emphasis as well as some development of particular physical capacities.